2022
DOI: 10.1155/2022/2023500
|View full text |Cite|
|
Sign up to set email alerts
|

MDH1 and MDH2 Promote Cell Viability of Primary AT2 Cells by Increasing Glucose Uptake

Abstract: Background. Acute lung injury (ALI) is a clinical disease with high morbidity and mortality, with limited treatment means. For primary alveolar epithelial type II (AT2) cells, glycolysis is an essential bioenergetic process. However, the significance of AT2 cell glycolysis in sepsis ALI remains unknown. Methods and Results. In the current study, based on microarray analysis, real-time quantitative PCR, and Western blotting, we found that the hsa00020: citrate cycle pathway was inactivated, specifically its dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…MDH1 can promote the viability of alveolar epithelial type II cells by promoting glucose intake, suggesting that targeting MDH1 may be a potential therapeutic strategy for patients with acute lung injury. 12 In addition, the MDH1-mediated malate-aspartate NADH shuttle maintains the activity levels of fetal liver hematopoietic stem cells. 13 Recent studies have shown that MDH1 can regulate autophagy and is required to maintain the level of the autophagy promoter unc-51 like autophagy activating kinase 1 (ULK1), and the activity of MDH1 increases after autophagy induction.…”
Section: Introductionmentioning
confidence: 99%
“…MDH1 can promote the viability of alveolar epithelial type II cells by promoting glucose intake, suggesting that targeting MDH1 may be a potential therapeutic strategy for patients with acute lung injury. 12 In addition, the MDH1-mediated malate-aspartate NADH shuttle maintains the activity levels of fetal liver hematopoietic stem cells. 13 Recent studies have shown that MDH1 can regulate autophagy and is required to maintain the level of the autophagy promoter unc-51 like autophagy activating kinase 1 (ULK1), and the activity of MDH1 increases after autophagy induction.…”
Section: Introductionmentioning
confidence: 99%
“…The expression levels of MDH1 and MDH2 are high in patients with lung cancer [ 4 , 10 ]. High expression of MDH1 is significantly correlated with patient survival, and its knockdown affects cell viability compared with that of MDH2 [ 10 , 11 ]. A previous report presented LW1497 , a dual inhibitor of MDH1 and MDH2, which showed significant in vivo antitumor effects against colon cancer through the inhibition of mitochondrial respiration and hypoxia-inducible factor-1 alpha (HIF-1α) accumulation [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%